Elite status maintained: a 12-year physiological and performance follow-up of two Olympic champion rowers - Mikulic, P.; Bralic, N. (Journal of Sports Sciences, 2018)
This case study reports the results of a 12-year (2005-2016) follow-up study of two Olympic champion rowers. The rowers were prospective athletes at the junior level when the study began, and we monitored their relevant physiological and performance data annually. Our findings indicated that their V.O2max gradually increased up to about 22 years of age and leveled off at a value of approximately 7 l/min with minimal fluctuations thereafter. However, the variables that directly influence the V.O2max changed. There was an age-related decline in maximal heart rate of about 0.5 beats/year, while oxygen pulse, which serves as an indirect measure of stroke volume, correspondingly increased by about 1 ml O2/beat per year, allowing the athletes to maintain exceptional V.O2max values. Maximal minute power of the studied rowers, derived each year from their ramp-wise tests, closely resembled the mean power output sustained during the 2000-m all-out tests on a rowing ergometer. A 12-year improvement of 28% and 33% occurred for the mean power output sustained over 2000 and 6000-m on a rowing ergometer, respectively. The findings contribute to the body of knowledge on athletes representing the true elites of their respective sports.